IMPLEMENTASI FUNGSI MANAJEMEN DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI MADRASAH MUTAWASITHAH PESANTREN HAMALATUL QUR'AN SINTANG - Sukhaimi, Heri; Al Mufti, Muflihin; Supangat, Supangat (UNISAN JURNAL, 2025)
This study aims to (1) determine the implementation of management functions in improving the quality of educators at Madrasah Mutawasithah Pesantren Hamalatul Qur'an Sintang, and (2) identify the supporting and inhibiting factors in improving the quality of educators. This research uses a descriptive qualitative method with a phenomenological approach. The data collection methods used are interviews, observations, and documentation. Data analysis techniques in this study include data reduction, data presentation, and drawing conclusions. The data sources used in this study are the head of the madrasah, educators, and the pesantren administrators. The results of the study show that the implementation of management functions at Madrasah Mutawasithah Pesantren Hamalatul Qur'an Sintang, including planning, organizing, implementation, and supervision, is running well in efforts to improve the quality of educators. Well-structured and clear educational planning helps in enhancing the educators' quality. Effective organizing, such as clear task delegation and the preparation of training schedules, facilitates the management of educators. The implementation of regular training and coaching programs also supports the improvement of educators' professional skills. Regular supervision ensures that all management processes run according to the set goals. Significant supporting factors in improving the quality of educators include the support from pesantren leaders, adequate facilities for training, and the involvement of educators in professional development programs. Meanwhile, inhibiting factors include limited budgets for further training and a lack of available time for educators to participate in development programs. The implications of this study are (1) the importance of the role of the head of the madrasah in leading, organizing, and evaluating the learning process and professional development of educators, (2) the need to improve the facilities and infrastructure that support training activities, (3) addressing inhibiting factors to ensure that the improvement of educators' quality can be carried out more effectively.